DEFINITION OF ACCEPTABLE DEGREE OF INDEPENDENCE OF THE MEMBERS OF THE HOLDING - Anna V. Zagranovskaia (Статистика и экономика)
The article offers the method of determining the extent of centralization of management, in a vertically-integrated holding, which will increase the competitiveness of participants of the integrated corporate structure due to minimal intervention of the parent company in the activities of the subsidiaries in setting the policy of purchases/sales of products domestic sales.